Risk Factor Analysis in Diabetes and Hypertension Patients from Odisha, India: A Cross-Sectional Study - Mohapatra, Prabhudatta; Debata, Ashrumochan; Pradhan, Rohan Kumar; Rath, Karmajeet; Mangaraj, Swayamsidha; Kar, Mihir Kumar; Kar, Durga Madhab (Indian Journal of Pharmaceutical Education and Research)
Objectives: This study aims to investigate the incidence of poor glycemic control among elderly diabetic individuals with hypertension in urban areas of Odisha, India. This observational cross-sectional study was conducted in an urban area of Odisha involving individuals with a diabetes duration of over five years. Materials and Methods: Participants were categorized into two groups based on their glycemic control status: those with good control (HbA1C<7%) and those with poor control (HbA1C≥7%). Multivariate analysis was employed to identify independent determinants. Results: Poor glycemic control was detected in 70.15% of 449 patients with diabetes for more than five years, indicating substantial relationships between numerous variables and glycemic control. A multivariate logistic regression study indicated significant links with poor glycemic control in people with diabetes mellitus. Participants who cohabitated with a partner had an increased risk of poor glycemic control (p=0.02). Financial dependence was identified as a protective factor, considerably lowering the risk of poor glycemic control (p=0.02). Among the study participants, the number of patients with chronic co-morbidities particularly hypertension and hyperlipidaemia were comparatively higher than only diabetic conditions. In contrast, poor medication adherence substantially increased the risk of poor glycemic control (p=0.04). Conclusion: The study highlights the significant impact of factors such as a lack of social support, poor medication adherence, and the presence of hypertension on poor glycemic control in diabetics, emphasising the importance of targeted interventions to address these issues and improve treatment outcomes.
Keywords: Glycemic Control; HbA1C; Diabetes; Hypertension